Re-forming Networks Through "Looping": An Ecological Approach to a Teacher’s Incorporation of New Technologies in Early Childhood (LEARNing Landscapes, 2013)
In this article, we discuss a teacher’s agency and digital pedagogy who, following a four-year Learning with Laptops professional development initiative, relocated from a Grade Six to a Grade One class. An ecological perspective on teacher agency combined with Actor Network Theory underscores the "repertoires for manoeuvre" available to teachers (Priestley et al., 2012, p. 211). The early childhood classroom presented unique openings for "looping" elements of the teacher’s previous network into a new context. Through re-forming networks, new spaces for digital pedagogy materialized.
Keywords: technology; agency; teacher; pedagogy; digital; Actor Network Theory; ecological; looping; network; early childhood